Preparation method of C4 selective hydrogenation catalyst

Al2O3-ZrO2 composite support was prepared by solid phase grinding method and impregnated with nickel salt and copper salt to form a carbon four-selective hydrogenation catalyst, which solved the problem of poor stability of existing catalysts under industrial conditions, and achieved high activity, good selectivity and Effects of sulfur resistance.

CN119488914AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311032400.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-21
Estimated Expiration
2043-08-16

AI Technical Summary

Technical Problem

It is difficult for existing non-precious metal catalysts to maintain stable catalytic performance under industrial conditions, especially in the presence of sulfide impurities in the liquid phase carbon four raw materials, resulting in a degradation of active site blocking and catalytic performance.

Method used

The composite support Al2O3-ZrO2 was prepared by solid phase grinding method, and the support was fully impregnated by a mixed solution of nickel salt and copper salt to form a carbon four-selective hydrogenation catalyst. This method improves the specific surface area of ​​the support and the abundance of the pore structure, and reduces the influence of sulfur adsorption on catalyst activity.

Benefits of technology

The high specific surface area, wide pore size and rich pore structure of the catalyst are achieved, which improves hydrogenation activity and monoolefin selectivity, reduces the hydrogenation loss rate of butene, and enhances catalytic stability and sulfur resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488914A_ABST
    Figure CN119488914A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a C4 selective hydrogenation catalyst, and belongs to the technical field of preparation methods of C4 fraction selective hydrogenation catalysts. A C4 selective hydrogenation catalyst in the prior art has the problems of poor sulfur resistance, low catalytic activity and low selectivity. The method comprises the following steps: (1) grinding and uniformly mixing solid aluminum salt and solid zirconium salt in a mortar; (2) ammonium bicarbonate is added and ground into uniform paste, and the molar ratio of ammonium bicarbonate to (Al + Zr) is (3-5): 1; 3) drying the mixture for the first time, washing with deionized water until the mixture is neutral, and drying for the second time; (4) roasting to obtain a composite carrier Al2O3-ZrO2; 5) preparing a mixed solution of nickel salt and copper salt, and fully impregnating the composite carrier with the mixed solution, and 6) drying and roasting the impregnated composite carrier to obtain the C4 selective hydrogenation catalyst.The C4 selective hydrogenation catalyst with good catalytic activity, stability and selectivity is obtained, and the preparation method is simpler and less in wastewater amount compared with a precipitation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing a C4 selective hydrogenation catalyst, belonging to the technical field of methods for preparing a C4 fraction selective hydrogenation catalyst. Background Art

[0002] When liquid mixed C4 raw materials are used for alkylation production, they need to go through a selective hydrogenation unit to selectively remove ppm-level butadiene (1000~20000 ppm) in the raw materials before entering the alkylation reaction unit to prevent butadiene from polymerizing under the action of concentrated sulfuric acid, resulting in a decrease in acid concentration and affecting the stable operation of the unit. The selective hydrogenation catalyst currently used in industry is a Pd-based catalyst supported by alumina, but due to the high price and scarcity of palladium metal, the development of a non-precious metal catalyst has a high strategic significance.

[0003] In the existing non-precious metal 1,3-butadiene selective hydrogenation reaction, non-precious metal catalysts usually have good butadiene selective hydrogenation activity and monoolefin selectivity, but a major challenge faced by this series of catalysts is that under industrial conditions, it is difficult for the catalyst to maintain stable catalytic performance during long-term operation. The reason is that under actual industrial operating conditions, liquid C4 feedstock usually comes from a catalytic cracking unit, so the feedstock contains sulfide impurities of more than ten to tens of ppm. 2- Due to its nucleophilic properties, it is easier to adsorb on the metal surface than butadiene, resulting in the closure of active sites. The catalytic performance gradually decreases with the extension of the reaction cycle. In addition, as crude oil faces the development of inferior quality, the sulfide content in the raw materials shows an increasing trend year by year.

[0004] Literature research shows that using catalytic cracking carbon four as raw material, at a reaction temperature of 70 °C, a reaction pressure of 1.3 MPa, and a liquid space velocity of 18 h -1 Under the conditions of 20 hours of continuous reaction, the Ni / Al2O3 catalyst began to show obvious deactivation after 20 hours of continuous reaction. After 70 hours of reaction, the catalyst activity decreased from nearly 100% to 70% (Liu Jianjun, Huang Xingliang, Petrochemical Engineering, 2011, 40(08): 825-830.). In addition, studies have found that the acidity of the carrier alumina will lead to the formation of green oil during hydrogenation. Therefore, the method of increasing the calcination temperature is often used to reduce the acidity of the alumina carrier to achieve the inhibition of green oil formation. However, too high a calcination temperature will cause the specific surface area of ​​the alumina carrier to decrease and the pore structure to collapse. Since C4 hydrogenation usually adopts the liquid phase feed method, an inappropriate pore structure will lead to the diffusion of the product being hindered, causing the occurrence of secondary reactions and reducing the selectivity of monoolefins.

[0005] In the prior art, patent CN105642324B discloses a method for preparing a 1,3-butadiene selective hydrogenation catalyst, which is composed of an active component amorphous nickel phosphide, an alumina carrier and an additive X. The catalyst preparation requires hydrothermal evaporation, inert atmosphere roasting, high-temperature hydrogen reduction and passivation processes at 75-100 °C, a total pressure of 1.5-2.0 MPa, and a space velocity of 5-10 h -1 , under the condition of hydrogen / butadiene molar ratio of 1.0-2.0, the butadiene conversion rate in mixed C4 is >98%, and the butene loss rate is <1%. CN106582706B discloses a method for preparing a nickel-based butadiene selective hydrogenation catalyst, wherein the catalyst uses alumina as a carrier, the main active component is Ni, and Ag, Au, Ce, and K are auxiliary active components, and has good butadiene hydrogenation activity and low butene loss rate. Both technical solutions do not solve the problem that S impurities and the like are adsorbed on the metal surface during use, resulting in the closure of active sites, nor do they solve the problem that the pore structure of the carrier alumina is fragile due to the suppression of green oil. In other prior arts, the monoolefin selectivity of non-precious metal catalysts is also poor. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a C4 selective hydrogenation catalyst with good sulfur resistance, high catalytic activity and high monoolefin selectivity.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a C4 selective hydrogenation catalyst, characterized in that it comprises the following steps: 1) Solid aluminum salt and solid zirconium salt are placed in a mortar and ground and mixed evenly, wherein the molar ratio of Zr to Al is 0.1~1:1; 2) Add ammonium bicarbonate and grind until it becomes a uniform paste, wherein the molar ratio of ammonium bicarbonate to (Al+Zr) is 3-5:1; 3) After the mixture is dried once, it is washed with deionized water until it becomes neutral and then dried twice; 4) Calcination to obtain the composite carrier Al2O3-ZrO2; 5) preparing a mixed solution of nickel salt and copper salt, wherein the molar ratio of Cu to Ni is 0.1-0.5:1, the total volume of the mixed solution is the same as the total pore volume of the composite support, and the composite support is fully impregnated with the mixed solution; 6) The impregnated composite carrier is dried and calcined to obtain a C4 selective hydrogenation catalyst.

[0008] The solid phase grinding method is used to prepare the carrier, which greatly reduces the amount of wastewater generated compared to the traditional precipitation method. The carrier has a higher specific surface area, a wider pore size and a richer pore structure, thereby reducing the effect of sulfur adsorption on the metal surface on the catalyst activity. The catalyst has a high loading capacity, high catalytic activity and high monoolefin selectivity. Drying, washing and drying are performed first to make the mixture initially condensed to prevent the weak Al-O-Zr bond from breaking due to direct washing with deionized water.

[0009] Preferably, the aluminum salt in step 1) is one or both of aluminum nitrate nonahydrate and aluminum chloride hexahydrate.

[0010] Preferably, the zirconium salt in step 1) is zirconium oxychloride octahydrate.

[0011] Preferably, the primary drying in step 3) is carried out at 60-120° C. for 20-25 h, and the secondary drying is carried out at 60-120° C. for 10-12 h.

[0012] Preferably, the calcination in step 4) is carried out in a muffle furnace at 400-600° C. for 4-6 hours.

[0013] Under optimal conditions, the proportion of Al2O3 in the composite carrier can reach 29.3~78.8wt%; the proportion of ZrO2 can reach 21.2~70.7wt%, ensuring the richness of the carrier pore structure and a high specific surface area, with a high pore volume and pore size.

[0014] Preferably, the nickel salt in step 5) is nickel nitrate hexahydrate.

[0015] Preferably, the copper salt in step 5) is copper nitrate trihydrate.

[0016] Preferably, the calcination in step 6) is carried out in a muffle furnace at 400-600° C. for 4-6 hours.

[0017] Under preferred conditions, NiO accounts for 5~20 wt% in the C4 selective hydrogenation catalyst; CuO accounts for 0.5~10wt%; and Al2O3-ZrO2 accounts for 70~94.5wt%.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: compared with precious metal catalysts, the manufacturing cost of the catalyst is greatly reduced; and the higher specific surface area, wider pore size and richer pore structure are beneficial to the diffusion of raw materials and products in the liquid phase C4 hydrogenation reaction and the reduction of the occurrence of secondary reactions, which greatly improves the hydrogenation activity and monoolefin selectivity, and the butene hydrogenation loss rate is low; at the same time, it also has better catalytic stability and good sulfur resistance; less wastewater is generated and the preparation method is simpler. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 These are the long-cycle reaction evaluation results of the C4 selective hydrogenation catalyst of Example 2. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments, and Embodiment 4 is the best embodiment of the present invention.

[0021] Example 1 A method for preparing a C4 selective hydrogenation catalyst comprises the following steps: 1) 37.5g aluminum nitrate nonahydrate and 32.2g zirconium oxychloride octahydrate were placed in a mortar and ground to mix evenly; 2) Add 47.4g of ammonium bicarbonate and grind until it becomes a uniform paste; 3) The paste sample was dried at 60°C for 24 h, then washed with deionized water until neutral, and dried again at 60°C for 12 h; 4) Calcination at 500°C for 5h in a muffle furnace to obtain the composite support Al2O3-ZrO2; 5) 3.09 g of nickel nitrate hexahydrate and 0.24 g of copper nitrate trihydrate are dissolved in deionized water to obtain a mixed solution, 15 g of the composite support is taken, the volume of the mixed solution is the same as the total pore volume of the composite support used, and the composite support is fully impregnated with the mixed solution; 6) The impregnated composite carrier was dried at 60°C for 12 h and calcined in a muffle furnace at 400°C for 4 h to obtain a C4 selective hydrogenation catalyst.

[0022] Example 2 A method for preparing a C4 selective hydrogenation catalyst, based on Example 1, wherein the amount of aluminum nitrate nonahydrate in step 1) is set to 112.5 g, the amount of zirconium oxychloride octahydrate is set to 10.7 g; the amount of ammonium bicarbonate in step 2) is set to 79.1 g. The amount of nickel nitrate hexahydrate in step 5) is set to 16.68 g, the amount of copper nitrate trihydrate is set to 6.5 g, the drying temperature in step 6) is set to 120° C., and the calcination is set to 600° C. for 6 hours.

[0023] Other conditions are the same as in Example 1.

[0024] Example 3 A method for preparing a C4 selective hydrogenation catalyst, based on Example 1, wherein the amount of aluminum nitrate nonahydrate in step 1) is set to 93.8 g, the amount of zirconium oxychloride octahydrate is set to 16.1 g; the amount of ammonium bicarbonate in step 2) is set to 118.6 g. The amount of nickel nitrate hexahydrate in step 5) is set to 10.28 g, the amount of copper nitrate trihydrate is set to 3.1 g, the drying temperature in step 6) is set to 80° C., and the calcination temperature is set to 500° C. for 6 hours.

[0025] Other conditions are the same as in Example 1.

[0026] Example 4 A method for preparing a C4 selective hydrogenation catalyst is provided. Based on Example 1, in step 1), aluminum nitrate nonahydrate is set to aluminum chloride hexahydrate, and the dosage is set to 60.5 g, and other conditions are the same as in Example 1.

[0027] Comparative Example 1 A method for preparing a C4 selective hydrogenation catalyst is provided. Based on Example 1, in step 1), the amount of aluminum nitrate nonahydrate is set to 5 g, the amount of zirconium oxychloride octahydrate is set to 120 g, and other conditions are the same as in Example 1.

[0028] Comparative Example 2 A method for preparing a C4 selective hydrogenation catalyst is provided. Based on Example 1, in step 1), the amount of aluminum nitrate nonahydrate is set to 120 g, the amount of zirconium oxychloride octahydrate is set to 5 g, and other conditions are the same as in Example 1.

[0029] Comparative Example 3 A method for preparing a C4 selective hydrogenation catalyst is provided. Based on Example 1, the amount of ammonium bicarbonate used in step 2) is set to 10 g, and other conditions are the same as those in Example 1.

[0030] Comparative Example 4 A method for preparing a C4 selective hydrogenation catalyst, based on Example 1, the aluminum nitrate nonahydrate and zirconium oxychloride octahydrate in step 1) are dissolved in 150 g of deionized water, the ammonium bicarbonate in step 2) is dissolved in 100 g of deionized water, and then poured into the mixed solution in step 1), gradually forming a white precipitate and continuously stirring for 1 hour, and step 3) is changed to filtering and washing the white precipitate in step 2) three times, and then drying at 60°C for 24 hours, and other conditions are the same as in Example 1. The precipitation method is used to prepare the carrier. The water consumption is large.

[0031] Performance Testing The pore structure of the composite carrier obtained in the preparation process of the above-mentioned embodiment and comparative example was analyzed, and the test results are shown in Table 1 below.

[0032] Table 1 Pore structure .

[0033] The catalysts prepared in the examples and comparative examples were loaded into a fixed bed reactor, and the selective hydrogenation of the catalytic C4 fraction containing 0.56% butadiene by mass fraction was continuously performed. The long-term reaction stability test results of Example 2 are shown in Figure 1 The hydrogenation performance test results of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 2 below.

[0034] Table 2 Hydrogenation performance test .

[0035] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a C4 selective hydrogenation catalyst, characterized in that: The following steps are involved: 1) Solid aluminum salt and solid zirconium salt are placed in a mortar and ground and mixed evenly, wherein the molar ratio of Zr to Al is 0.1~1:1; 2) Add ammonium bicarbonate and grind until it becomes a uniform paste, wherein the molar ratio of ammonium bicarbonate to (Al+Zr) is 3-5:1; 3) After the mixture is dried once, it is washed with deionized water until it becomes neutral and then dried twice; 4) Calcination to obtain the composite carrier Al2O3-ZrO2; 5) preparing a mixed solution of nickel salt and copper salt, wherein the molar ratio of Cu to Ni is 0.1-0.5:1, and the total volume of the mixed solution is the same as the total pore volume of the composite support; and fully impregnating the composite support with the mixed solution; 6) The impregnated composite carrier is dried and calcined to obtain a C4 selective hydrogenation catalyst.

2. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The aluminum salt in step 1) is one or both of aluminum nitrate nonahydrate and aluminum chloride hexahydrate.

3. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The zirconium salt described in step 1) is zirconium oxychloride octahydrate.

4. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The primary drying in step 3) is carried out at 60-120° C. for 20-25 hours, and the secondary drying is carried out at 60-120° C. for 10-12 hours.

5. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The calcination in step 4) is carried out at 400-600° C. in a muffle furnace for 4-6 hours.

6. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The nickel salt described in step 5) is nickel nitrate hexahydrate.

7. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The copper salt described in step 5) is copper nitrate trihydrate.

8. The method for preparing the C4 selective hydrogenation catalyst according to claim 1, characterized in that: The calcination in step 6) is carried out in a muffle furnace at 400-600° C. for 4-6 hours.

Citation Information

Patent Citations

  • Preparation method and application of a compound carrier metal nanometer catalyst

    CN101143326A

  • Preparation method of alkyne-containing C4 hydrogenation catalyst

    CN113663688A

  • Catalyst as well as preparation method and application thereof

    CN115739098A

  • Nickel-based catalyst for methanation of carbon monoxide and carbon dioxide and preparation method thereof

    CN115888724A

  • Ammonia deposition precipitation process for producing a copper-nickel / gamma-alumina catalyst, said catalyst and its use in the conversion of exhaust gases

    US20210394162A1